Examining farm-level perceptions, costs, and benefits of small water harvesting structures in Dewas, Madhya Pradesh [India] - Malik, Ravinder Paul Singh; Giordano, Meredith A.; Sharma, V. (Elsevier, 2014)
A recent initiative in Madhya Pradesh, India to promote privately funded, rainwater harvesting structures on farmers' own land has shown substantial economic and livelihood benefits. In contrast to the many poorly functioning, community managed rainwater harvesting programs, the individual or decentralized rainwater harvesting structures have led to significant improvements in availability of irrigation water, are vival of the agricultural economy of the region, and substantial increases in farmer incomes and livelihoods. Since 2006, more than 6000 farmers in the state have invested in on-farm ponds. The investments are highly cost effective and farmers are able to recover their initial investment in approximately 3 years. While longer-terms impact studies are needed, this initial assessment suggests that on-farm rainwater harvesting ponds are a promising private small irrigation option in Madhya Pradesh and similar regionsin India and elsewhere.